Reliability of timber bridges using nailed plywood box beams - Stamato, Guilherme Correa [UNESP]; Calil Jr., Carlito; Martinez, Mariano Espinosa; Da Fonte, Thalita Fernandes (My University, 2006)
The Nailed Box Beam structural efficiency is directly dependent of the flange-web joint behavior, which determines the partial composition of the section, as the displacement between elements reduces the effective rigidity of the section and changes the stress distribution and the total displacement of the section. This work discusses the use of Nailed Plywood Box Beams in small span timber bridges, focusing on the reliability of the beam element. It is presented the results of tests carried out in 21 full scale Nailed Plywood Box Beams. The analysis of maximum load tests results shows that it presents a normal distribution, permitting the characteristic values calculation as the normal distribution theory specifies. The reliability of those elements was analyzed focusing on a timber bridge design, to estimate the failure probability in function of the load level.
Keywords: Beam elements; Box beam; Characteristic value; Effective rigidity; Failure Probability; Full scale; Joint behavior; Load levels; Maximum load; Structural efficiencies; Timber bridge; Normal distribution; Plywood; Stress concentration; Timber; Wood products; Wooden bridges; Reliability